Sustainable goal setting: a large-scale case in management practice. Issue 8 (13th November 2017) - Deschamps, Carl; Mattijs, Jan
Abstract : Purpose: The purpose of this paper is to give evidence of effective, large-scale, and time-sustained goal setting through the use of performance indicators (PIs) in managing a fairly large and decentralized social-security organization, despite indications that the motivational effects of goal setting are hard to sustain in the long term. Design/methodology/approach: The authors analyze five years of monthly organizational performance data across 30 regional offices and five activities to identify the links between PIs and productivity. Findings: The authors identify correlations that demonstrate a cycle where low performance scores on indicators increase productivity in the next period, but high performance decrease it, thus renewing the cycle. Research limitations/implications: While long-term gains in the productivity are not the direct product of goal setting, the close relationship between goals and productivity illustrates the motivational potential of communicable targets and close feedback that led to a culture of performance within the organization. Practical implications: The case studied demonstrates how a performance management system can be designed and managed so that long-term fatigue is avoided while maintaining a dynamic workforce that adapts in the face of environment change by increasing its efforts as needed. Originality/value: This paper answers a call to connect management control studies with managerial work done in practical settings.